Synergistic effect of anethole and doxorubicin alleviates cell proliferation, cell cycle arrest, and ER stress and promotes ROS-mediated apoptosis in triple-negative breast cancer cells - Arumugam, Poornima; Sampathkumar, Banupriya; Perumalsamy, Haribalan; Balusamy, Sri Renukadevi; Ramesh, Vignesh; Sundaravadevel, Sumathi (Journal of Biochemical and Molecular Toxicology, 2021)
The heterogeneity and poor prognosis of triple-negative breast cancer (TNBC) have limited the treatment options and made clinical management challenging. This has nurtured a major effort to discover druggable molecular targets. Currently, chemotherapy is the primary treatment strategy for this disease. Doxorubicin is the most frequently used chemotherapeutic drug for TNBC and due to the fact that chemotherapeutic drugs have a lot of side effects, we evaluated the synergistic effect of the phytocompound anethole and doxorubicin. The cytotoxic effect of anethole in combination with doxorubicin on MDA-MB-231 cells was evaluated by various parameters, including apoptosis, cell cycle analysis, DNA damage, and cell proliferation. Furthermore, mitochondrial membranepotential (MMP), endoplasmic reticulum (ER) stress, and reactive oxygen species (ROS) levels were also evaluated in the cells treated with/without anethole and doxorubicin. Expression of the apoptotic proteins was evaluated by Western blot analysis. Initial evaluation of cytotoxicity of anethole on MDA-MB-231 cells demonstrated preferential suppression of cell proliferation and when treated along with doxorubicin it showed enhanced cytotoxicity with a synergistic effect. Cell cycle analysis revealed arrest at different stages of the cell cycle, such as sub G0-G1, G0-G1, S, and G2M in various treatment groups and apoptotic cell death was subsequently evident with propidium iodide (PI) staining. The synergistic action of anethole and doxorubicin effectively induced mitochondrial membrane potential loss, which, in turn, led to a burst of ROS production, which eventually produced unfolded protein response by damaging the ER. Synergistic anticancer effect was observed on exposure of MDA-MB-231 cells to anethole and doxorubicin in inducing cell death.
CRIS-Team WoS Importer:2021-10-08